Perancangan Prototipe Sistem Pembelajaran Digital Berbasis Arsitektur Moodle Terintegrasi dengan ELUMAK: Design of a Digital Learning System Prototype Based on Moodle Architecture Integrated with ELUMAK - Yuda Ferdiansyah; Darman Darman; Zila Razilu (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
The digital transformation in education has created an urgent need for an online learning system that is not only efficient but also integrated and easy to use by both lecturers and students. In this context, the use of Learning Management Systems (LMS) such as Moodle often faces challenges, particularly due to interface complexity, limited personalization, and limited integration with existing campus academic systems. This research focuses on designing a prototype digital learning system based on the Moodle architecture integrated with ELUMAK at Muhammadiyah University of Kendari. The goal is to improve the effectiveness, convenience, and user experience in the online learning process. This research uses a User-Centered Design (UCD) approach through the stages of understanding the context of use, determining user needs, designing solutions, and evaluating the design. These stages are realized through identifying user needs, designing interfaces using Figma, and evaluating usability using the System Usability Scale (SUS) instrument. A total of 30 respondents, comprising lecturers and students, participated in the trial to assess the extent to which the system meets their needs. The test results showed an average SUS score of 76.42, which falls in the "Good" to near "Excellent" range. These findings indicate that the designed system is highly easy to use, responsive to user needs, and has the potential to improve the integration of academic data across platforms in higher education environments. Thus, the implementation of the UCD approach has proven effective in producing an e-learning system design that is intuitive, adaptive, and supports the digital transformation of education.